Archivos y Numismática: el tesoro de áureos de Duarría (Castro del Rey, Lugo) - Rodríguez Casanova, Isabel (Revista General de Información y Documentación, 2009)
Comparison between documentation preserved in some spanish archives has allowed to improve our knowledge about the Duarría gold coin hoard, very bad known since today. We can also indentify ten of these coins, that were kept in the Gabinete Numismático of the Museo Arqueológico Nacional until the Civil Spanish War.
Keywords: Coin-hoards; Archives; Aurei; Roman Imperial Coinage; Duarría (Castro del Rey; Lugo); Monetary circulation; Northwest Area